AN ANALYSIS OF ENGLISH SPEAKING ACTIVITIES FROM BAHASA INGGRIS THINK GLOBALLY ACT LOCALLY BOOK - Aprilia Riyana Putri; Titik Ulif Hidayati (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2022)
Learning a foreign language is very necessary, especially English, which has an important role in the world of education, business, work and others. In learning English, there are four skills that must be possessed by students, namely, speaking, writing, reading, and listening. To master these skills, it is necessary to have methods, media, or others to support these activities. The use of textbooks in learning activities, especially learning English, plays an important role. Therefore, this study aims to investigate the speaking activities contained in the textbook entitled Bahasa Inggris Think Globally Act Locally for the ninth grade of junior high school. The contents of this textbook are described and analyzed using a descriptive-qualitative method. The source of the data for this study was taken from a textbook entitled Bahasa Inggris Think Globally Act Locally for the ninth grade of junior high school. The data that has been collected is analyzed through several stages, namely: (1) grouping the data into types of speaking activities (Acting from Script, Communication Games, Discussions, Prepared Talk, Questionnaires, and Simulation and Role Play), (2) identifying the kinds of speaking activities that are most dominant. The results of this study indicate that in the textbook entitled Bahasa Inggris Think Globally Act Locally for the ninth grade, there are six speaking activities and they are dominated by Prepared Talk speaking activities.